Cancer morbidity among polishers. Issue 2 (May 1982) - Järvholm, B; Thiringer, G; Axelson, O
Abstract : The mortality pattern among 86 men was determined to investigate the possible hazards of polishing steel. The men had polished steel with polishing paste for at least five years. The polishing pastes had contained tallow, beeswax, carnauba wax, alundum, carborundum, ferric oxide, and chalk. A total of 18 men had died compared with 13.3 expected. Four had died of stomach cancer compared with 0.44 expected (p less than 0.005). The mortality for other causes of death was not increased. The study does not permit any definite conclusion but indicates a possible cancer hazard among polishers.